Numerical investigation of cement interface debonding in deviated shale gas wells considering casing eccentricity and residual drilling fluid. (October 2022) - Gu, Chenwang; Li, Xiaorong; Feng, Yongcun; Deng, Jingen; Gray, Kenneth
Abstract: In shale gas development, the problem of sustained casing pressure has become more and more prominent. A major cause of sustained casing pressure is the debonding of cement sheath. The main reasons for cement interface debonding include the cumulative plastic deformation of the cement sheath and the pressure buildup in the interface. In this work, considering the hardening and shrinking of the cement sheath, a finite-element model for evaluating the sealability of the cement interface during the whole life cycle of a well is constructed. The evolution of the cement interface failure is studied. Through a comprehensive parametric analysis, the influence of well trajectory, casing eccentricity, and cement sheath voids on the debonding of cement sheath is studied. Meanwhile, the influence of the pressure of the residual drilling fluid within the cement sheath is also investigated. The results show that the shrinkage of the cement sheath is the main factor that causes the debonding of the cement interface. The size of the micro-annulus of the debonding interface increases as the internal casing pressure decreases. The influence of wellbore trajectory on cement sheath debonding is not significant, while casing eccentricity and cement sheath voids have a larger impact. With the increase of casing eccentricity and cement sheath voids, the size of the micro-annulus increases. As the temperature of the cement sheath during the hydraulic fracturing process decreases, the pressure in the trapped residual drilling fluid decreases, causing the increase of the size of the micro-annulus. This paper establishes a new model of cement sheath integrity for the whole life cycle of a well considering various engineering and geological characteristics. The method provides a favorable basis for predicting the failure of wellbore integrity caused by cement sheath debonding, and provides usefully guidance for engineering operations.